2014
DOI: 10.1155/2014/989574
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Vascular Architecture and Angiogenesis with Pituitary Adenoma Histotype

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic factor in solid tumors. However, its role in angiogenesis in pituitary adenoma is controversial. Angiogenesis in solid tumors including pituitary adenoma is commonly evaluated by microvascular density (MVD). Here, we evaluated MVD and the role of VEGF in vascular architecture in 51 pituitary adenomas (24 nonfunctioning, 13 prolactin-secreting, 10 growth hormone-secreting, 3 adrenocorticotropic hormone-secreting, and 1 thyroid-stimulating hormone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
1
20
1
2
Order By: Relevance
“…In this context, the spatial relationship between the capillaries and the endocrine cells plays an important role regulating their secretory function. Previous reports have shown that microvascular density of pituitary tumours is smaller than in normal pituitary gland, and the density varies with adenoma histotypes234.…”
mentioning
confidence: 88%
“…In this context, the spatial relationship between the capillaries and the endocrine cells plays an important role regulating their secretory function. Previous reports have shown that microvascular density of pituitary tumours is smaller than in normal pituitary gland, and the density varies with adenoma histotypes234.…”
mentioning
confidence: 88%
“…Some previous studies have investigated angiogenesis in PitNETs [11][12][13][17][18][19][20][21][22][23]. However, research specifically studying the role of the different elements of the TME in the modulation of PitNET neovascularisation is scarce [24], contrasting with the extensive data available for other cancers [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Объем удаленной в ходе операции опухоли в этих случаях, как правило, сопоставим с объемом визуализирующихся аденом гипофиза, однако возникают объективные сложности с получением материала для гистологического исследования, связанные с потерей ткани в ходе нейрохирургических манипуляций. Мы не нашли в литературе данных для сравнения с нашими результатами, поскольку исследования строения и свойств сосудов ранее проводилась в основном в макроаденомах гипофиза (в нашем исследовании лишь 27% опухолей приходилось на макроаденомы) [12,13]. К тому же, в таких исследованиях применялась разная методика оценки свойств сосудов, отличались и единицы площади исследуемых областей, что прежде всего связано с разным оптическим разрешением микроскопов и программным обеспечением.…”
Section: Discussionunclassified
“…Широко используемым методом оценки строения и свойств сосудов в опухолях человека является подсчет микрососудов с помощью специфических маркеров эндотелиальных клеток, таких как CD31 и CD34. Выбор иммуногистохимического маркера для оценки строения и свойств сосудов аденом основан на опыте ранее проведенных работ [12][13][14].…”
Section: Discussionunclassified